Late-season Glufosinate applications to manage herbicide-resistant Palmer amaranth in soybean - LALIT MOHAN, FNU (My University, 2026)
Palmer amaranth (Amaranthus palmeri S. Watson) is among the most economically detrimental weed in U.S. soybean production, and the accumulation of herbicide resistance across multiple sites of action has reduced the number of consistently effective postemergence options available to growers. In Kansas, glufosinate and 2,4-D choline applied in Enlist E3 soybean remain important postemergence tools for managing resistant populations. However, two practical challenges can limit their reliability: single glufosinate applications often fail to control large Palmer amaranth, and glufosinate efficacy is sensitive to environmental conditions at the time of spraying. This thesis investigated both problems through replicated field experiments conducted at two Kansas locations during 2024 and 2025. The first study compared single and sequential postemergence applications of glufosinate (0.59 kg ai ha-1) alone and with 2,4-D choline (0.53 kg ae ha-1) targeting 20 to 30 cm Palmer amaranth. Sequential programs outperformed single applications in both years, improving control by 3.6 percentage points in 2024 (99 versus 95%; p < 0.0001) and 12 percentage points in 2025 (98 versus 86%; p < 0.0001). Neither the herbicide composition, application sequence, nor interval between passes (3, 10, or 14 days) influenced final control among sequential programs. At Hays in 2025, where treatment separation was greatest, sequential programs also resulted in greater yield than single applications (1,459 versus 1,143 kg ha-1; p = 0.0006) and reduced Palmer amaranth biomass (12.8 versus 45.6 g m-2; p = 0.001). These results indicate that the second application was more important than herbicide composition or interval within the sequential programs evaluated. The second study tested whether Delta-T, a single-value index of atmospheric evaporative demand calculated from dry-bulb and wet-bulb temperature, could predict glufosinate performance under field conditions. Glufosinate alone and with 2,4-D choline were each applied at 93 and 187 L ha1 across multiple dates to capture a range of Delta-T values. At Manhattan 2024, where conditions spanned both optimal and high Delta-T (3.7 to 12.8 C), applications within the recommended 2 to 8 C range achieved 92% control with minimal variability, while applications above 8 C averaged only 59% with high plot-to-plot inconsistency. Each 1 C increase in Delta-T reduced control by 3.9 percentage points. At Hays 2025, however, all applications fell within the optimal Delta-T window, yet mean control reached only 68%. At this site, adding 2,4-D choline (73 versus 61%) and increasing carrier volume (75 versus 59%) both improved outcomes. Low pre-application rainfall and reduced solar radiation, not spray-day Delta-T, explained the poor performance. At Manhattan 2025, where environmental conditions were consistently favorable, all treatments achieved 87% control regardless of herbicide composition or carrier volume. Delta-T is a practical field tool for deciding when to spray, but it cannot account for the cumulative environmental stress a weed population has experienced before the sprayer arrives.
Keywords: Palmer Amaranth; Herbicide; Weed Control; Delta T